2016
DOI: 10.1007/s12035-016-0272-x
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Aerobic Exercises Improve Spatial Memory in Aging Rats Through Stimulating Distinct Neuroplasticity Mechanisms

Abstract: Aging is associated with impaired cognition and memory and increased susceptibility to neurodegenerative disorders. Physical exercise is neuroprotective; however, the major evidence of this effect involves studies of only aerobic training in young animals. The benefits of other exercise protocols such as strength training in aged animals remains unknown. Here, we investigated the effect of aerobic and strength training on spatial memory and hippocampal plasticity in aging rats. Aging Wistar rats performed aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 82 publications
3
54
0
3
Order By: Relevance
“…Moreover, BDNF suppression, by injecting TrkB-FC, inhibited the increase of p75 NTR expression after axotomia reducing the neuronal survival 33 . Only one study found on aged rats that, following 8 weeks of endurance training, the p75 NTR level increased in parallel with an enhancement of BDNF expression 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BDNF suppression, by injecting TrkB-FC, inhibited the increase of p75 NTR expression after axotomia reducing the neuronal survival 33 . Only one study found on aged rats that, following 8 weeks of endurance training, the p75 NTR level increased in parallel with an enhancement of BDNF expression 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that exercise improves mood and cognition, accelerating hippocampal neurogenesis in humans and in animal models. Voluntary wheel running correlates with an increase in the gene expression of neurotrophins and other growth factors [1,2], markers of synaptic plasticity, and downregulation of inflammatory factors [3], enhancing cognitive functions [4,5]. Beside its pro-cognitive role, exercise improves mood and libido but little has been known about why it has such a profound effect on the brain [6].…”
Section: Introductionmentioning
confidence: 99%
“…Weiterhin konnte in anderen Studien beobachtet werden, dass eine Reduktion der Muskelmasse einen direkten Einfluss auf die Atrophie zerebraler Strukturen hat, was auch auf diesem Weg eine Verminderung kognitiver Funktionen bedingt [46] [47]. Zudem werden altersbedingte neurokognitive Veränderungen (Verschlechterungen) von peripheren Sarkopenie-bedingten Abbauprozessen katalysiert [43] [60]. Diese relativ neue Studie zeigte, dass aerobe Übungen eher die glutamatergen Signalwege modulieren, wobei Krafttraining Veränderungen in der Proteinkinase C (PKC: spielt wichtige Rolle bei der zellulären Signalweiterleitung) und in inflammatorischen Prozessen begünstigt [60] und somit in der Prävention und Therapie von neurodegenerativen Funktionen differenziert angewendet werden sollte (hierzu wird jedoch noch weitere Forschung benötigt).…”
Section: Krafttraining In Der Onkologieunclassified